A rare congenital cystic malformation of the oral cavity requiring OOPS (operation on placental support) procedure at delivery. (18th April 2012) - Thomas, T; Thomson, A; Kubba, H; Ledingham, MA
Abstract : An 18 year old para1+0 was referred to our fetal medicine unit with an intraoral cystic structure (22mm×19mm) detected at routine anomaly scan. Fetal MRI confirmed a large thin walled cyst (25mm×24mm×18mm) in the midline filling the entire oral cavity and inseparable from the tongue. Differential diagnosis included congenital ranula, epidermoid cyst, unilocular lymphatic malformation and enteric duplication cyst. Multidisciplinary team counselling was performed involving fetal medicine specialists, neonatologists, paediatric ENT surgeons and paediatric anaesthetists and a management plan formulated. Ultrasound monitoring through the course of the pregnancy revealed no significant change in the size of the cyst. Development of polyhydramnios suggested that the cyst was beginning to interfere with fetal swallowing raising the possibility of potential problems with securing and maintaining airway at delivery. Hence delivery was arranged by elective caesarean section at 38+ weeks under steroid cover. Operation On Placental Support (OOPS) procedure was done at the time of delivery with the cyst being decompressed and intubation done while placental circulation was maintained. Excision of the lesion was performed on day 2 and histology confirmed a thyroglossal duct cyst. The baby did well in the neonatal period and was discharged home in the first week of life. With this case report we seek to highlight management of this extremely rare congenital cystic malformation of the oral cavity and the crucial role of combined imaging and multidisciplinary input to ensure a good outcome.